Implementasi Program Klampid New Generation (KNG) pada Pelayanan Administrasi Kependudukan Kelurahan Panjang Jiwo Kota Surabaya - Maji, Hendri; Hardjati, Susi (VISA: Journal of Vision and Ideas, 2025)
This research aims to determine the implementation of the Klampid New Generation (KNG) Program in population administration services in Panjang Jiwo Village, Surabaya City. The Klampid New Generation (KNG) program is designed to make it easier for people to access population administration services, such as issuing birth certificates, death certificates, updating biodata on family cards, and other population documents. This research uses a qualitative descriptive method. The data collection technique was carried out using the triangulation method, namely through interviews, literature study and documentation. The research results show that the implementation of the Klampid New Generation (KNG) Program in population administration services in Panjang Jiwo Village has gone well, referring to the policy implementation theory put forward by George C. Edward III.